Pengaruh Insentif dan Kedisiplinan terhadap Kinerja dengan Religiuitas Sebagai Variabel Moderating - Muhammad Nasri Katman; Muh Rasul Pradana; Rahman Ambo Masse (Jurnal Ekonomi & Bisnis, 2022)
This study aims to prove or determine the partial and simultaneous effect of incentives and discipline on the performance of PT. Independent Distribution Partners with religiosity as a moderating variable. The method used is a quantitative method with quantitative descriptive. The sample used is 45 respondents. The data collected consists of primary and secondary data. Data analysis using SPSS version 25 application. The results of this study indicate that partially incentives have a positive effect on performance, discipline has no positive effect on performance and religiosity has a positive effect on performance. Simultaneously, each shows a significant effect on performance. Religiosity is able to moderate the relationship between incentives and discipline on the performance of PT. Mitra Distribusi Mandiri.